The Influence of ESG Disclosure And Board Size on The Financial Performance of Public Manufacturing - Suliestiyowati SW, Indri (LP2M IAIN Palopo, 2025)
This study aims to explore the relationship between ESG and Board Size with the financial performance of public companies. And focuses on analyzing whether public companies better financial performance in terms of profitability. Research Methods Companies listed on the Indonesia Stock Exchange (IDX) that have annual reports and insulin recommendations that can be accessed. The number of samples taken will be adjusted to the availability of data that meets the criteria above. It is estimated that around 15 to 35 companies were active during the study period. The results of data analysis examining the influence of Environmental, Social, and Governance (ESG) disclosure and Board Size on corporate financial performance, using multiple linear regression analysis with SPSS software. The analysis begins with descriptive statistics to illustrate the distribution of all three variables across 175 samples. Classical assumption tests—including normality, heteroscedasticity, and multicollinearity tests—were conducted to ensure the reliability of the regression model, with results indicating no violations of these assumptions. The regression results reveal that ESG disclosure has a significant negative effect on financial performance, while Board Size has a significant positive effect. These findings are supported by partial t-tests and simultaneous F-tests, both of which yielded statistically significant results at a 95% confidence level. The coefficient of determination (R²) was found to be 30.5%, indicating that the independent variables explain 30.5% of the variation in financial performance, with the remainder influenced by other factors not included in the model. These findings provide valuable insights for managerial decision-making and corporate policy development that consider ESG aspects and board governance